A Global Perspective on Public Relations Professionalism: Mapping the Structure of Public Relations Associations' International Networks. (September 2014) - Yang, Aimei; Taylor, Maureen
Associations play a powerful role in socializing practitioners. The presence of public relations associations across the world is one more step toward professionalization for the entire profession. This study examines the structure of global public relations professionalization manifested through the networks among international and national public relations professional associations. The findings of a cross-national, multilevel network analysis suggest that despite the overall dominance of international public relations associations, at the regional level, local centers have also emerged. In addition, European public relations associations have developed more relationships with other national, regional, and international associations than American-based professional associations.